Absolute income inequality and rising house prices. (29th June 2019) - Goda, Thomas; Stewart, Chris; Torres García, Alejandro
Abstract: Income inequality and house prices have risen sharply in developed countries during 1975–2010. In line with theoretical models, we argue that this co-movement is no coincidence, but that inequality has driven up house prices on the grounds that it raises the aggregate demand for housing. Our results suggest that absolute inequality and house prices in most Organisation for Economic Co-operation and Development (OECD) countries were positively correlated and cointegrated, whereas relative inequality and mean income were not significant long-run determinants. This finding indicates that the surge in OECD house prices in part can be explained by a top-income-induced increase in housing demand, and that it is important to consider the interaction of rising mean income and its relative distribution when studying potential correlates of house prices. Moreover, our results confirm previous findings that the short-term real interest rate also is an important correlate of house prices.